Influence of physical activity with moderate and vigorous intensities on the muscle strength of dynapenic older adults: Prospective study - Dos Santos, V. R. [UNESP]; Muniz, C. F. [UNESP]; Gobbo, L. A. [UNESP] (Elsevier, 2021)
Introduction: Aging causes certain physical changes such as a decline in muscle strength, called dynapenia. Physical activity with moderate and high intensity is effective for increasing and maintaining muscle strength, thus physical activity could be an alternative for preventing dynapenia in older adults. The aim this study was to analyze the association between the practice of moderate and vigorous physical activity (MVPA) and muscle strength of non-dynapenic and dynapenic older adults in a 12-month follow-up. Methods: The study included 110 Brazilians older adults aged 60 to 91 (70 ± 7) years of both sexes. The variables investigated were: muscle strength, performed by the handgrip dynamometer test, and MVPA evaluated by a triaxial accelerometer. Results: It was verified that the older adults who maintained the practice of at least 30 minutes of MVPA daily during the 12-month follow-up presented protection for dynapenia (OR:0.15; CI:0.04-0.54), regardless of sex. Furthermore, it was observed that dynapenic older adults who increased the daily minutes of MVPA presented protection for reduction in muscle strength over the follow-up (OR:0.18; CI:0.04-0.69), regardless of sex and age. Conclusion: The practice of MVPA prevents muscle strength decline in dynapenic older adults, regardless of sex and age.
Influence de l'activité physique d'intensités modérées et vigoureuses sur la force musculaire des personnes âgées dynapéniques: étude prospective
Keywords: Accelerometry; Aging; Physical activity; Strength